2001
DOI: 10.4322/rbcv.2015.228
|View full text |Cite
|
Sign up to set email alerts
|

Suscetibilidade de Lymnaea columella Say, 1817 à infecção por Fasciola hepatica L., 1758

Abstract: São apresentadas as espécies Lymnaea columella Say, 1817 da família Lymnaeidae Rafinesque e Stenophysa marmorata (Guilding, 1828) da família Physidae Fitzinger, como as únicas espécies dos respectivos gêneros, encontradas no Estado do Rio de Janeiro. Após a identificação das espécies que ocorriam neste Estado, o estudo foi direcionado para a identificação das espécies de moluscos que possuíam real potencial como hospedeiro intermediário de Fasciola hepatica L., 1758, avaliação da suscetibilidade a miracídios d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The infection rates of 40.2 and 47% obtained were similar to those of Dacal et al (1988) for Belo Horizonte snails. The mean mortality rates up to 60 days (33.5% and 41.1%) were similar to those obtained by other authors (Gomes 1985, Dacal et al 1988. High mor- Rates of infection and mortality, 60 days after exposure to miracidia tality (100%) in the first experiment was observed after 44 days in the exposed snails and after only 34 days in the control group.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The infection rates of 40.2 and 47% obtained were similar to those of Dacal et al (1988) for Belo Horizonte snails. The mean mortality rates up to 60 days (33.5% and 41.1%) were similar to those obtained by other authors (Gomes 1985, Dacal et al 1988. High mor- Rates of infection and mortality, 60 days after exposure to miracidia tality (100%) in the first experiment was observed after 44 days in the exposed snails and after only 34 days in the control group.…”
Section: Discussionsupporting
confidence: 80%
“…In Brazil, Gomes (1985) obtained mean of infection rates of 27.6% when L. columella from Rio de Janeiro were exposed to three miracidia and 11% when each snail were exposed to 5 miracidia, at room temperatures of 27-29ºC. The mean mortality was 60.8%.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Through considering morphological characteristics alone, Rezende et al (1973) had previously identified L. (Galba) cubensis in the state of Rio de Janeiro, in the municipalities of Três Rios, Paraíba do Sul, Petrópolis and Teresópolis, Brazil. However, Gomes & Serra-Freire (2001) questioned the validity of this record because this species had never been found in these municipalities previously. Unfortunately, those studies did not present the geographical coordinates of the sampling points, which makes it difficult to localize these specimens in order to elucidate this question.…”
Section: Discussionmentioning
confidence: 97%